A cidadania no livro didático de matemática: um diagnóstico a partir dos temas transversais trabalho e consumo - Oliveira, Paulo Roberto Vieira de (2004)
The present studies main objective was to identify how the concept of citizenship presents itself in the Didactics Book of Mathematics. The mediation between citizenship and mathematics happens through the transversal themes work and consumption, which came through the generating themes of Paulo Freire. Fifth to eighth grade books of Mathematics, which have been recommended by the National Program of the Didactics Book in the years 1999 and 2001, have been analyzed and their exercises were classified according to the Learning Environments proposed by Skovsmose. The results suggest that some relevant themes for society, which are subjected to discussion in the scope of Mathematics Education, are not found in the Didactics Book of Mathematics. Almost all questions were centered in Literacy, reinforcing the need of an approach that considers Literacy, Materacy and Technoracy as it is proposed by D Ambrosio. Some initial steps towards tax calculus have been identified, but the discussion of their importance in society, which would enable deeper debate between mathematics and society, has not evolved